The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1213/01.ane.0000117150.29361.5a
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Uncontrolled Hemorrhagic Shock After Liver Trauma: Fatal Effects of Fluid Resuscitation Versus Improved Outcome After Vasopressin

Abstract: Although IV fluid administration is the mainstay of nonsurgical management of trauma patients with uncontrolled hemorrhagic shock, the efficacy of this strategy has been discussed controversially. In this animal model of severe liver trauma with uncontrolled hemorrhagic shock, vasopressin, but not saline placebo or fluid resuscitation, improved short-term survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
8

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(55 citation statements)
references
References 22 publications
1
46
0
8
Order By: Relevance
“…Most animal models for uncontrolled hemorrhagic shock achieve blood withdrawal by tail amputation [14], or liver or spleen laceration [15,16]. These procedures greatly influence the rate and the amount of blood loss and require a long period of anesthetic or fasting state.…”
Section: Discussionmentioning
confidence: 99%
“…Most animal models for uncontrolled hemorrhagic shock achieve blood withdrawal by tail amputation [14], or liver or spleen laceration [15,16]. These procedures greatly influence the rate and the amount of blood loss and require a long period of anesthetic or fasting state.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies demonstrate that vasopressin increases blood pressure and prevents hypovolemic cardiac arrest from fatal hemorrhage. (11,12) In addition, to improve perfusion pressure of vital organs, exogenous administration of vasopressin provides the added benefit of enhancing clot formation. (13) Therefore, it seems reasonable to consider vasopressin for treating hemorrhagic shock patients at the scene.…”
Section: Discussionmentioning
confidence: 99%
“…(8)(9)(10) Vasopressin is a potent vasopressor with extended purposes in the treatment of severe trauma, septic shock, cardiac diseases and during cardiopulmonary resuscitation. (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) In addition, a few researchers have found that vasopressin is absorbed well via the mucosa of the airway and alveoli. (23)(24)(25) The combination of a LMA and vasopressin could be a practical management tool in pre-hospital settings.…”
Section: Introductionmentioning
confidence: 99%
“…These volumes are equivalent to more than twice the normal blood volumes (i.e., >12 L in adult human subjects). Resuscitation with such a large volume of fluid is difficult to achieve, especially under combat conditions, and a rapid increase in blood pressure during resuscitation is detrimental for the trauma victim with uncontrolled hemorrhage (16). In view of this, to resuscitate the animals we used Ringer's lactate in volumes equal to the lost blood to make the study more relevant clinically.…”
Section: Effects Of Am/ambp-1 In a Rat Model Of Controlled Hemorrhagementioning
confidence: 99%